2021
DOI: 10.3389/fpsyg.2021.629650
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Exploration of Landscape Preferences Based on Naturalness and Visual Openness for College Students With Different Moods

Abstract: The interaction between man and nature causes people to have different preferences for their surrounding environment, and pleasant landscapes can bring both physical and mental benefits to people. Previous studies have demonstrated the relationship between moods and landscape preferences, and this study sought to explore the landscape preferences of college students under different moods. A total of 1,034 students participated in the survey, recovering 1,022 valid questionnaires. The Profile of Mood States (PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 64 publications
0
5
0
1
Order By: Relevance
“…Furthermore, it seems that mental states can also influence landscape preferences in terms of their naturalness and openness. People in a fatigued state [ 65 ] have a greater preference for landscapes with a higher naturalness and those in an indignant state have a greater preference for relatively private, less-open landscapes. Our data are consistent with the findings by de Groot and van den Born [ 2 ], who showed that the majority of Dutch respondents preferred an attractive environment, where the greatness and power of nature can be experienced.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it seems that mental states can also influence landscape preferences in terms of their naturalness and openness. People in a fatigued state [ 65 ] have a greater preference for landscapes with a higher naturalness and those in an indignant state have a greater preference for relatively private, less-open landscapes. Our data are consistent with the findings by de Groot and van den Born [ 2 ], who showed that the majority of Dutch respondents preferred an attractive environment, where the greatness and power of nature can be experienced.…”
Section: Discussionmentioning
confidence: 99%
“…This technology simulates multisensory experiences in natural environments, enabling the study of people's preferences for natural settings and their potential in stress reduction. By creating immersive experiences within virtual environments, VR technology achieves enhanced therapeutic outcomes [19][20][21].…”
Section: The Application Of Vr Technology In Landscape Restorationmentioning
confidence: 99%
“…CGSs provided natural spaces to meet university students' landscape preferences, which contributed to generating positive emotions among students in the university ( 54 , 55 ). Moreover, university students exposed to a preferred environment tend to have more positive emotions and lower negative emotions ( 51 ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%